The Lipid A from Rhodopseudomonas palustris Strain BisA53 LPS Possesses a Unique Structure and Low Immunostimulant Properties. Issue 15 (22nd December 2016) - Di Lorenzo, Flaviana; Palmigiano, Angelo; Albitar‐Nehme, Sami; Sturiale, Luisa; Duda, Katarzyna A.; Gully, Djamel; Lanzetta, Rosa; Giraud, Eric; Garozzo, Domenico; Bernardini, Maria Lina; Molinaro, Antonio; Silipo, Alba
Abstract: The search for novel lipid A analogues from any biological source that can act as antagonists, displaying inhibitory activity towards the production of pro‐inflammatory cytokines, or as immunomodulators in mammals, is a very topical issue. To this aim, the structure and immunological properties of the lipopolysaccharide lipid A from the purple nonsulfur bacterium Rhodopseudomonas palustris strain BisA53 have been determined. This lipid A displays a unique structural feature, with a non‐phosphorylated skeleton made up of the tetrasaccharide Man p ‐α‐(1→4)‐Glc p N3N‐β‐1→6‐Glc p N3N‐α‐(1→1)‐α‐Gal p A, and four primary amide‐linked 14:0(3‐OH) and, as secondary O ‐acyl substituents, a 16:0 and the very long‐chain fatty acid 26:0(25‐OAc), appended on the Glc p N3N units. This lipid A architecture is definitely rare, so far identified only in the genus Bradyrhizobium . Immunological tests on both murine bone‐marrow‐derived and human monocyte‐derived macrophages revealed an extremely low immunostimulant capability of this LPS lipid A. Abstract : On the trigger : The structure and the immunological properties of the lipopolysaccharide (LPS) lipid A from the bacterium Rhodopseudomonas palustris strain BisA53 have been determined. This lipid A has a novel structure in both the saccharide and lipid parts (see graphic), which confers the entire LPS with very weak immunostimulant activity towards both murine and human model systems employed.